A Landscape Approach for Detecting and Assessing Changes in an Area Prone to Desertification in Sardinia (Italy). (26th March 2008) - Giordano, Francesca; Marini, Alberto
Abstract : Land degradation and desertification processes represent a serious problem in many areas of Sardinia (Italy), as in the Nurra region where urbanization, overgrazing, and fires have induced environmental degradation and rapid land-use change. In this study, using satellite remote sensing and geographical information system, landcover and landscape change dynamics were investigated. Comparing two Landsat-5 Thematic Mapper, it was possible to assess landcover transformations, and with the FRAGSTATS software it was possible to quantify the changes of landscape characteristics in the Nurra region over a 10-years period. The images were classified into seven landcover types, and a stepwise indicator approach was adopted. The results show a decrease in cropland and an increase of forestland and urban areas. The overall change was estimated to be about 2.5% of the total study area, with two most frequent landcover conversion types: cropland to urban areas and cropland to forestland.